Covering the Uncovered: Complete Root Coverage of Gingival Recession using Sub-Epithelial Connective Tissue Graft - Subedi, Suraksha; Ranjit, Rebicca; Bista, Soni (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Gingival recession is defined as the displacement of marginal tissue apical to cementoenamel junction, exposing the root surface. It is caused by traumatic toothbrushing, periodontitis, high frenal attachment, and injudicious orthodontic tooth movement. It leads to dentinal hypersensitivity, aesthetic problem, root caries, cervical abrasion and difficulty in oral hygiene maintenance. This can be managed by root coverage procedure which can be achieved by various surgical techniques. This case report shows successful management of Miller’s Class II gingival recession using sub-epithelial connective tissue graft procedure that was followed up for six months without any complications.